Stereoselective synthesis of epoxides and diepoxides. Applications in total synthesis of natural products and analogues - García-Ruiz, María Cristina (Universidad de Málaga, Servicio de Publicaciones y Divulgación Científica, 2014)
The present work is on the total synthesis of the natural compounds and/or analogues of Bengamides, Gummiferol and Depudecin. The target molecules, selected in virtue of their prominent biological activity as antibiotic and antitumor agents are featured by the presence of one or two epoxide groups and were synthesized by application of a novel methodology of asymmetric epoxidation based on the use of a new class of chiral sulfur ylides. The aim of every total synthesis discussed in this thesis is to develop an efficient route to the final product in relation to the introduction of stereogenic elements. The biological background as well as the synthetic history of each target compounds will be introduced prior to discussion of the actual synthesis. Chapter 2 provides a comprehensive review of the current research status of bengamides and includes a brief introduction to the structure, classification and precedents together with their eminent role as antitumor agents. As main objective, the major part of this chapter summarizes the strategies and experimental approaches to a new class of bengamide analogues containing either one or two epoxides throughout the polyketide chain, that might mimic the mode of action of fumagillin. With the purpose of better understanding the mechanism of action exhibited by bengamides, azido derivative in position C4 will be also described. Finally, the biological evaluation of some of the analogues synthesized will be discussed.Chapter 3 describes the synthesis of gummiferol, a cytotoxic metabolite with antitumor activity that possesses two consecutive oxirane rings conjugated to a triacetylene moiety, by means of the use of chiral sulfur ylides. The isolation and characterization is described across this chapter as well as the synthesis of the natural product and analogues reported to date. In this way, the second objective will be to develop an alternative to the previous synthesis of gummiferol by generating the epoxides in a stereoselective fashion by means of the chiral sulfur ylide methodology. In Chapter 4, depudecin, a new microbial metabolite with promising antiangiogenic activity is presented together with its biological synthesis. Hence, our ultimate goal will be to stablish an efficient and straightforward route toward its total synthesis. A further chapter (Chapter 5) has been included, displaying additional synthetic projects carried out during this thesis. Hence, contributions to the synthesis of the natural products globomycin, epibestatin and celebeside A, as well as the protease inhibitor AcArgValArgArgCMK, are described by using the solid phase synthesis methodology. Finally, a summary of the outcome of this work, a general discussion and perspectives are provided in Chapter 6.
Keywords: Epóxidos - Síntesis - Tesis doctorales; Natural Products; Asymmetric Synthesis; Analogues; Epoxides; Chiral Sulfur Ylides